Inhibitors of Myosin Light Chain Kinase Block Synaptic Vesicle Pool Mobilization during Action Potential Firing - Ryan, Timothy A. (J Neurosci, 1999)
During repetitive action potential firing the maintenance of synaptic transmission relies on a continued supply of synaptic vesicles for fusion with the presynaptic plasma membrane. The mechanism of transport by which vesicles are delivered to the site of fusion from a reserve pool is unknown, as are the biochemical pathways linking intracellular Ca(2+) elevation with vesicle mobilization. Here, using the fluorescent tracer FM1-43 in hippocampal synaptic terminals, I show that inhibitors of myosin light chain kinase can block mobilization of the reserve pool and not the immediately releasable pool.